Terpaan Media Komunikasi Lingkungan dan Perubahan Perilaku: (Studi Korelasi Kampanye #Seasoldier Pada Followers) - Jayanti Wenas; Stella Stefany; Pincanny Poluan (Mediator: Jurnal Komunikasi, 2023)
High amount of plastic waste and its threats to the environment and living things have become a major concern for many countries. One of many causes is using single-use plastic bags throughout our everyday lives. Various studies have examined the negative impacts of plastic waste. Many environmental activists have been motivated to response this global concern. Seasoldier is one of the community who have been conducting a digital campaign by utilizing the hashtag #Seasoldier to encourage the followers in reducing their use of plastic bags. This study aims to determine the correlation between media exposure of #SeaSoldier on Instagram and behavioural change in their followers and to examine the Media Ecology theory in an environmental communication context. A purposive sampling technique was applied to obtain respondent with the following criteria: having an Instagram account and also an active follower of the Seasoldier. The result of this study indicates a positive and strong correlation between the use of hashtag feature toward the behavioural change with correlation coefficient value r=.776 and coefficient determination value of r2=.598 that defines 59.8% of hashtag campaign exposure to changing followers' behavior. Future researchs can develop broader research of changing factors in follower's behavior with qualitative method.